Sexual rights as human rights: a guide to authoritative sources and principles for applying human rights to sexuality and sexual health. - Miller, Alice M; Kismödi, Eszter; Cottingham, Jane; Gruskin, Sofia (Reproductive health matters, 2015)
This Guide seeks to provide insight and resources to actors interested in the development of rights claims around sexuality and sexual health. After engaging with the vexed question of the scope of sexual rights, it explores the rules and principles governing the way in which human rights claims are developed and applied to sexuality and sexual health, and how that development is linked to law and made a matter of state obligation. This understanding is critical to policy and programming in sexual health and rights, as it supports calling on the relevant range of human rights, such as privacy, non-discrimination, health or other universally accepted human rights, as well as demanding the action of states under their international and national law obligations to support sexual health.